Dampak penggunaan bungkil biji jarak (Jatropha curcas L.) dalam ransum sapi potong terhadap fermentabilitas dan kecernaan secara in vitro - Y.F. Caritas Pela Levi; Maya Dwisari; Hidayat Tanuwiria; Atun Budiman; Iman Hernaman (University of Insan Cendekia Mandiri, 2022)
Jatropha seed cake has potential as ruminant feed, but is constrained by the anti-nutritional and toxic substances contained in it. The aim of the research was to study the effect of using jatropha seed cake in beef cattle rations on fermentability and digestibility. In vitro evaluation was used to study the fermentability and digestibility of beef cattle rations containing 0%, 10%, 20%, 30%, and 40% of jatropha seed cake. The experiment used a completely randomized design followed by Duncan's multiple range test with 5 treatments which were repeated 4 times. The variables measured were ammonia, volatile fatty acids, dry matter digestibility and organic matter digestibility. The treatment of rations containing jatropha seed cake resulted in significant changes in fermentability and digestibility (P<0.05), where the use of 20% treatment resulted in the highest of ammonia, volatile fatty acids, dry matter digestibility and organic matter digestibility (P<0.05), namely 3.69 mM, 163.58 mM, 77.88 % and 70.35%, respectively. The conclusion of this research is the use of jatropha seed cake as much as 20% produces the best fermentability and digestibility.